Alat Ukur Kadar Air Biji-bijian Secara Mobile Berbasis Internet Of Things Sebagai Indikator Kualitas Komoditas Barang Dagang - Zidane Walid, Kholiq; Firmawati, Nini (Universitas Andalas, 2025)
Research has been conducted on a mobile IoT-based moisture content measuring device as an indicator of the quality of cocoa beans, yellow coffee, and robusta coffee. Moisture content is extremely important in maintaining the quality of beans because it directly affects their quality, taste, aroma, shelf life, and safety for consumption. This device uses a Capacitive Soil Moisture Sensor to detect moisture content by measuring changes in capacitance caused by dielectric changes. The moisture measuring device consists of a Capacitive Soil Moisture Sensor as the moisture sensor, an ESP32 as the data processor, an LCD to display the moisture content percentage, an LED as an indicator of high moisture levels, and a Smartphone as a measurement database through Blynk. The device was tested by measuring the moisture content of three types of grain samples: cocoa beans, yellow coffee, and robusta coffee. Each sample consisted of 10 variations of moisture content measured using a comparison tool, the Cerra Tester. The average measurement error percentages were found to be 3.02% for yellow coffee, 3.12% for cocoa beans, and 3.35% for robusta coffee. From the researchresults, the designed tool is as expected and works well.